1973
DOI: 10.1080/00221325.1972.10533155
|View full text |Cite
|
Sign up to set email alerts
|

Constructional Variety in the Spoken Language of School Children

Abstract: Uncertainty scores (H and relative H) were computed for the verbs, noun phrases, and sentences produced by 180 children between the ages of 5 and 13 years on a story-telling task. Linear age trends occurred for Sentence H and relative H and for Noun-phrase H (though not relative H), but not for verb H and relative H. There were no overall sex differences, but measure-specific age-by-sex interactions and higher-order age trends. Uncertainty scores of the type proposed, if suitably refined, may measure the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…."). (Harmann, 1976;Hass & Wepman, 1973;MBB, 1983, November;Poole. 1979 (MWYG, 1983, July;Wood, 1966).…”
Section: Verb Phrases Verbsmentioning
confidence: 99%
“…."). (Harmann, 1976;Hass & Wepman, 1973;MBB, 1983, November;Poole. 1979 (MWYG, 1983, July;Wood, 1966).…”
Section: Verb Phrases Verbsmentioning
confidence: 99%
“…Loban (Note 9) reported that expressions of tentativeness including supposition, hypothesis, and conditionality are associated with effective users of language from kindergarten through sixth grade. Hass and Wepman (1973) similarly found that uncertainty increased as a function of age in children S to 13 years old and noted that "there are many fine points about the uncertainty scores [with regard to the Age X Sex interaction] that demand further investigation" (p. 305). Baumann (1976) analyzed 7| hours of tape of adults in various settings for confirmatory tag questions and qualifying prefatory statements.…”
Section: Topicmentioning
confidence: 99%
“…Winitz (1959). Number of Words (Hass and Wepman, 1973;Jones and McMillan, 1973;Longhurst and Grubb, 1974), Total Number of One Word Responses (Lovell, Hoyle, Sidall, 1968;Minifie, Darley and Sherman, 1963), and Mean Number of Words in Five Longest Responses (Minifie et al, 1963) are all methods of word counting used to determine levels of language development.…”
Section: Statement Of Purposementioning
confidence: 99%